Pengaruh Penggunaan Kredit Perbankan dan Pertumbuhan Industri Manufaktur Terhadap Pertumbuhan Ekonomi Indonesia - Indah Sulistiyani; Retno Muslinawati (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to determine the effect of the use of bank credit and the growth of the manufacturing industry on economic growth in Indonesia. There are two independent variables, namely banking credit and the manufacturing industry, and the dependent variable, namely economic growth. The method used in this research is descriptive with a quantitative approach. The type of data in this study is time series data with a time period from 2011-2021. Data sources were obtained through the Indonesian Central Bureau of Statistics and Banking Statistics. The analysis technique applied in this study is multiple linear regression. The analysis tool used was Eviews 12. The results showed that the use of bank credit had a positive and significant effect on economic growth. The manufacturing industry growth variable has a negative and insignificant effect on economic growth in Indonesia.